2013
DOI: 10.1246/cl.2013.266
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Polymer Recognition Based on Semiartificial Helical Polysaccharide

Abstract: Two kinds of polymeric nanoarchitectures, i.e., one-dimensional polymer composites and two-dimensional sheet-like structures, can be created using a semiartificial helical polysaccharide with one-dimensional cavities and peripheral molecular-recognition sites.The creation of precise polymer assemblies at the nanometer scale, which could lead to novel chemical and physical properties, depending on their assembly modes, is of great concern because of their potential applications as fundamental nanomaterials. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This chirality gives the helix an obvious role in recognition, which is well demonstrated by the α-helices present in the Zinc finger motif for its binding to DNA double helix or proteins. [2][3][4] Taking the polyvalence of the helical structure as inspiration, chemists have applied synthetic helices to different areas [5][6][7] such as nanomaterials, [8][9][10] chiral recognition, [11][12][13][14] and catalysis. [15][16][17][18][19] In the field of nanomaterials, using nature's building blocks, Lecommandoux and coworkers investigated the synthesis and self-assembly of polypeptide-based diblock copolymers into different nanostructures and studied their possible application as stimuli-responsive materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This chirality gives the helix an obvious role in recognition, which is well demonstrated by the α-helices present in the Zinc finger motif for its binding to DNA double helix or proteins. [2][3][4] Taking the polyvalence of the helical structure as inspiration, chemists have applied synthetic helices to different areas [5][6][7] such as nanomaterials, [8][9][10] chiral recognition, [11][12][13][14] and catalysis. [15][16][17][18][19] In the field of nanomaterials, using nature's building blocks, Lecommandoux and coworkers investigated the synthesis and self-assembly of polypeptide-based diblock copolymers into different nanostructures and studied their possible application as stimuli-responsive materials.…”
mentioning
confidence: 99%
“…Taking the polyvalence of the helical structure as inspiration, chemists have applied synthetic helices to different areas such as nanomaterials, chiral recognition, and catalysis. In the field of nanomaterials, using nature’s building blocks, Lecommandoux and co-workers investigated the synthesis and self-assembly of polypeptide-based diblock copolymers into different nanostructures and studied their possible application as stimuli-responsive materials. To replicate the properties of cell-penetrating peptides (CPPs), which have excellent membrane permeability in part as a consequence of their helical shape, Wu and co-workers reported that rapid cellular internalization was observed for PEGylated left-handed helical poly­(phenyl isocyanide) corona micelles. , However, such assemblies are usually prepared by methods that are time- and resource-consuming and give solutions with a relatively low content of polymer.…”
mentioning
confidence: 99%